2018
DOI: 10.1002/we.2198
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of variation management strategies for wind power integration in different electricity system contexts

Abstract: Variation management strategies improve the capability of the electricity system to meet variations both in the electricity demand and in the generation that relies on variable energy sources. In this work, we introduce a new, functionality‐based, categorization of variation management strategies: shifting (eg, batteries), absorbing (eg, power‐to‐gas), and complementing (dispatchable generation, including reservoir hydropower) strategies. A dispatch model with European coverage (EU‐27 plus Norway and Switzerla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 26 publications
(32 reference statements)
0
37
0
Order By: Relevance
“…The analysis and description of the different TES units in this paper use the VMS categories of shifting, absorbing, and complementing technologies, as defined by Göransson and Johnsson (2018). In brief, a shifting VMS is short-term and operates within one sector, where it stores energy for later use or moves the demand in time (e.g.…”
Section: Variation Management Strategies (Vms)mentioning
confidence: 99%
“…The analysis and description of the different TES units in this paper use the VMS categories of shifting, absorbing, and complementing technologies, as defined by Göransson and Johnsson (2018). In brief, a shifting VMS is short-term and operates within one sector, where it stores energy for later use or moves the demand in time (e.g.…”
Section: Variation Management Strategies (Vms)mentioning
confidence: 99%
“…Mileva et al [13] show that high levels of solar generation in the electricity system can be cost-effectively integrated using a portfolio of technological options. Göransson and Johnsson [14] have shown that batteries are typically the preferred option for intra-day storage that spans over a couple of hours, while wind power generation needs storage for longer periods of variation [14].…”
Section: Introductionmentioning
confidence: 99%
“…Solar power and wind power require different types of flexibility from the electricity system, since the fluctuations in their electricity generation differ in characteristics. Solar power needs mainly storage for 6-12 h (to store electricity between day-time and night-time) while wind power exhibits fluctuations in electricity generation over a time period up to several days, and for some regions there is also a need to store large volumes of electricity between seasons [3].…”
Section: Introductionmentioning
confidence: 99%